INVESTIGATION OF INFLUENCE OF FACTORS ON FIRE RESISTANCE OF PARTITIONS MADE OF SANDWICH PANELS - Danchenko, Y.; Kachkar, Y.; Rashkevich, N. (Municipal economy of cities (Technical science), 2023)
The authors describe the results of studies of thermal processes in partitions made of sandwich panels under one-sided influence of fire. Analysis of the thermal state of multilayer partitions with mineral wool plates and development of recommendations for the design of buildings from such structures is possible using the simulation of thermal processes that occur during fire exposure to the studied samples. There is a certain number of models of the thermal state of multilayer partitions with mineral wool plates of different levels of complexity and purpose. However, in these models there are parameters that are individual for each partition and are known with insufficient accuracy. The authors provided an improved mathematical model of heat conduction in partitions, the difference of which is the application of heat transfer coefficients from the unheated surface of the partition in boundary conditions. A comparison of the fire resistance limits for a partition made of a sandwich panel indicates a strong influence of the accuracy of setting the heat transfer coefficient on the dependence of the thickness of the partition on the fire resistance limit. The accuracy of the task of the heat transfer coefficient on the dependence of the thickness of the partition on the fire resistance limit was scientifically substantiated, which showed a strong influence of the boundary condition describing the processes of heat transfer on the surface of the partition, which is not heated, on the accuracy of determining the limits of fire resistance of the structure under study. The influence of the accuracy of the assignment of the coefficient of heat transfer from the object to the environment on the fire resistance of the investigated building structures, which during the test are subject to both natural (mobility) of air and forced blowing, as, for example, during tests of air ducts with fire protection, must be taken into account convectively radiation heat exchange, which will allow to obtain the most accurate result regarding the determination of their fire resistance characteristics.